NLRR1 Is a Potential Therapeutic Target in Neuroblastoma and MYCN-Driven Malignant Cancers - Takatori, Atsushi; Hossain, MD. Shamim; Ogura, Atsushi; Akter, Jesmin; Nakamura, Yohko; Nakagawara, Akira (Frontiers in Oncology, 2021)
Receptor tyrosine kinases (RTKs) receive different modulation before transmitting proliferative signals. We previously identified neuronal leucine-rich repeat 1 (NLRR1) as a positive regulator of EGF and IGF-1 signals in high-risk neuroblastoma cells. Here, we show that NLRR1 is up-regulated in various adult cancers and acts as a key regulator of tumor cell proliferation. In the extracellular domains of NLRR1, fibronectin type III (FNIII) domain is responsible for its function to promote cell proliferation. We generated monoclonal antibodies against the extracellular domains of NLRR1 (N1mAb) and screened the positive N1mAbs for growth inhibitory effect. The treatment of N1mAbs reduces tumor cell proliferation in vitro and in vivo, and sensitizes the cells to EGFR inhibitor, suggesting that NLRR1 is a novel regulatory molecule of RTK function. Importantly, epitope mapping analysis has revealed that N1mAbs with growth inhibitory effect recognize immunoglobulin-like and FNIII domains of NLRR1, which also indicates the importance of FNIII domain in the function of NLRR1. Thus, the present study provides a new insight into the development of a cancer therapy by targeting NLRR1 as a modulator of proliferative signals on cellular membrane of tumor cells.